Aplicação de polímero hidroretentor no desenvolvimento inicial de Eucalyptus grandis - Sanches, Luiz Vitor Crepaldi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The experiment was conducted in two stages, the first was composed by physicochemical characterization of the hydrogel in the laboratory and the second field test. Laboratory tests were performed at the UNESP - Univ Estadual Paulista, Campus of Botucatu/SP, Department of Natural Resources/Soil Science in Lageado Experimental Farm. The field test was implemented in August 2009 in Santa Clara farm (48º 40' 45 W and 23º 18' 47 S) in the city of Itatinga/SP. The polymer was studied Hydrosolo H ™ capable of retaining 500 ml of water per gram of polymer. The field experiment adopted the experimental design factorial 2 x 5 (2 modes of application and 5 polymer doses plus the control) in a randomized block design with four replications, plots with 49 plants, being 25 useful to analyse. The applications of hydrogel were performed on furrow and surface simulating the use with of the planter, and applicator with showerhead type, being used the quantities of polymer 0; 0,85; 1,50; 2,20; 2,90 and 3,60 g.plant-1. In laboratory was evaluated density, water holding capacity, pH and electrical conductivity of the hydrogel, and the experimental field were evaluated plant height, stem diameter relative chlorophyll index, and number of branches at planting, 15 and 30 days after transplantation. The survival rate, volume of water used in each treatment, number of irrigations needed, interval days between irrigations and operating costs and the polymer were measured after experiment. The polymer promoted great cost x benefit, because it occurred 100% survival of plants after 30 days of transplantation; reduced by 57% the number of irrigations needed to promote forest stand; increased the interval between irrigations, from 4 for 10 days; significant reduced in water consumption in irrigation both as per hectare or per plants, occurring savings of 58% (18,3 m3 ha-1), the operating cost of irrigation ...

O experimento foi realizado em duas etapas, a primeira foi composta pela caracterização físico-química do hidrogel em laboratório e a segunda pelo ensaio em campo. As análises laboratoriais foram realizadas no Departamento de Recursos Naturais/Ciência do Solo da Faculdade de Ciências Agronômicas, pertencente à Universidade Estadual Paulista Júlio de Mesquita Filho Campus de Botucatu/SP. O ensaio em campo foi implantado em agosto de 2009 na Fazenda Santa Clara (48º 40' 45 W e 23º 18' 47 S) localizada no município de Itatinga/SP. O polímero estudado foi o Hydrosolo H™ com capacidade de reter 500 ml de água por grama do polímero. No experimento em campo adotou-se o delineamento experimental fatorial 2 x 5 (2 modos de aplicação x 5 doses do polímero mais o controle) em blocos casualizados com 4 repetições, parcelas compostas por 49 plantas, sendo 25 úteis para avaliação. As aplicações de hidrogel foram realizadas na cova e via superficial simulando o uso com plantadeira e aplicador do tipo chuveirinho, sendo utilizadas as quantidades do polímero 0; 0,85; 1,50; 2,20; 2,90 e 3,60 g planta-1. Em laboratório foi avaliado a densidade, capacidade de retenção de água, pH e condutividade elétrica do hidrogel, em campo experimental foram avaliados a altura da planta, o diâmetro do caule, o índice relativo de clorofila e o número de ramos no plantio, e aos 15 e 30 dias após o plantio. O índice de sobrevivência, volume de água utilizado em cada tratamento, número de irrigações necessárias, intervalo de dias 2 entre as irrigações e os custos operacionais e do polímero foram mensurados ao fim do experimento. O polímero promoveu beneficio, pois com sua aplicação ocorreu 100% de sobrevivência das mudas após 30 dias do plantio; reduziu em 57% o número de irrigações necessárias para promover o povoamento florestal; aumentou o intervalo ...
Application of polymer hydrogel in the initial development of Eucalyptus grandis
Keywords: Eucalipto - Plantio; Acrilamida; Polímeros; Povoamento florestal; Plantas - Efeito de potássio; Eucalyptus grandis